Assessment of Multielement Extractants for Prediction of Available Potassium in Thai Soils - Surachet Aramrak,; Jongruk Chanchareonsook,; Chairerk Suwannarat,; Ed Sarobol, (Agriculture and Natural Resources, 2007)
In many countries, the efficiency of Mehlich 3 and ammonium bicarbonate – DTPA (ABDTPA) has long been elucidated as multielement extractants for simultaneous measurement of nutrient elements including potassium (K) in soils. However, information on their efficiencies for assessing the availability of K in Thai soils is still inadequate. This study was conducted to assess the efficiency of the two multielement extractants in predicting available K in some Thai soils. The relationships between the amounts of K extracted by Mehlich 3 and AB-DTPA with those extracted by NH4OAc, the conventional extraction method, widely used in soil testing laboratories in Thailand, and those taken up by corn was investigated. The results indicated that the amounts of K extracted by both Mehlich 3 and AB-DTPA were highly correlated to those extracted by NH4OAc (r = 0.969** and r = 0.894**, respectively) and those absorbed by corn (r = 0.930** and 0.902**, respectively). In addition, coefficient of determination (r2) for the relationship between amounts of K taken up by corn and extracted by the three extractants were 0.887 (NH4OAc), 0.866 (Mehlich 3), and 0.813 (AB-DTPA). Therefore, Mehlich 3 and AB-DTPA can be effectively used for determining K availability status in Thai soils. Nevertheless, Mehlich 3 was identified to be better measurement extractant than AB-DTPA.